2000
DOI: 10.1038/35041577
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of repulsion versus adhesion by different splice forms of an Eph receptor

Abstract: Eph tyrosine kinase receptors and their membrane-bound ephrin ligands mediate cell interactions and participate in several developmental processes. Ligand binding to an Eph receptor results in tyrosine phosphorylation of the kinase domain, and repulsion of axonal growth cones and migrating cells. Here we report that a subpopulation of ephrin-A5 null mice display neural tube defects resembling anencephaly in man. This is caused by the failure of the neural folds to fuse in the dorsal midline, suggesting that ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
274
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(290 citation statements)
references
References 28 publications
13
274
1
2
Order By: Relevance
“…An earlier study also showed that purified ephrin-A1 stimulated neurite outgrowth of spinal motor neurons (45). In addition, a truncated form of EphA7 mediates attractive interaction with ephrin-A5 in neural tube closure during development (47). The ventroward shift may reflect attractive interactions between EphA5(KϪ) transgene protein with the ligands in the septal target, in the absence of repulsive interactions caused by the inhibition of endogenous EphA receptors.…”
Section: Expression Of a Truncated Epha Receptor Alters Hippocampal Axonmentioning
confidence: 95%
“…An earlier study also showed that purified ephrin-A1 stimulated neurite outgrowth of spinal motor neurons (45). In addition, a truncated form of EphA7 mediates attractive interaction with ephrin-A5 in neural tube closure during development (47). The ventroward shift may reflect attractive interactions between EphA5(KϪ) transgene protein with the ligands in the septal target, in the absence of repulsive interactions caused by the inhibition of endogenous EphA receptors.…”
Section: Expression Of a Truncated Epha Receptor Alters Hippocampal Axonmentioning
confidence: 95%
“…Binding of clustered ephrin-A ligands to the full-length EphA7 receptor results in phosphorylation of its intracellular kinase domain, initiating a signaling cascade that results in cell repulsion (Holmberg et al, 2000). This prompted us to ask whether soluble EphA7 can affect ephrinA ligand-induced activation of full-length Eph receptor.…”
Section: Soluble Epha7 Blocks Ephrin-a4-mediated Activation Of Full-lmentioning
confidence: 99%
“…The individual function of EphA7 was assessed in the developing GT vasculature using a null EphA7 allele (Holmberg et al, 2000). A comparison of the GT vessel diameters between wild-type and EphA7 homozygous mutant embryos revealed no significant expansions of the GT vessels (Fig.…”
Section: Loss Of Epha7 Is Not Sufficient To Cause Gross Enlargement Omentioning
confidence: 99%